7v+6=5v+16

Simple and best practice solution for 7v+6=5v+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7v+6=5v+16 equation:


Simplifying
7v + 6 = 5v + 16

Reorder the terms:
6 + 7v = 5v + 16

Reorder the terms:
6 + 7v = 16 + 5v

Solving
6 + 7v = 16 + 5v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-5v' to each side of the equation.
6 + 7v + -5v = 16 + 5v + -5v

Combine like terms: 7v + -5v = 2v
6 + 2v = 16 + 5v + -5v

Combine like terms: 5v + -5v = 0
6 + 2v = 16 + 0
6 + 2v = 16

Add '-6' to each side of the equation.
6 + -6 + 2v = 16 + -6

Combine like terms: 6 + -6 = 0
0 + 2v = 16 + -6
2v = 16 + -6

Combine like terms: 16 + -6 = 10
2v = 10

Divide each side by '2'.
v = 5

Simplifying
v = 5

See similar equations:

| 5x+2y=117 | | 76=4x-8 | | 2x-10y+7=0 | | 35=11y+2 | | .5(6x-3)=.5(6+6x) | | -(7x+10)-10=-8(4+x) | | 2(c+6)=3G-6g | | x=3x-40 | | 7b=10b+18 | | 6(-10p-3)-8p=6(-12p-3)-4 | | v^2-4v-37=2 | | 24x-3(2x-5)=51 | | 73-x=86-2x | | (2x^2-3xy^2-y^2)-(3x^2-xy^2)= | | F(X)=20(0.9)x^6 | | 6m+9+7x-2= | | 9.25x=5.75x+40 | | 8w-12=(-4) | | -10+6m-m=-1+3m+5m | | 74t+28t-101t+16=89 | | 3n-6=3-5n-n | | 5+7-9-8=11 | | -4(w+1)=-20 | | -7y+14=-28 | | 5x^2+4x=-3 | | 4x-10=3x-4 | | -540+13p=1500 | | -67a+56a=99 | | 4n^2=256 | | 4x-30=130 | | 37a-73a+73a+-33a=100 | | -2a-2=0 |

Equations solver categories